The Politics of Foreclosures - AGARWAL, SUMIT; AMROMIN, GENE; BEN‐DAVID, ITZHAK; DINC, SERDAR (Journal of Finance, 2018)
ABSTRACT The U.S. House of Representatives Financial Services Committee considered many important banking reforms in 2009 to 2010. We show that, during this period, foreclosure starts on delinquent mortgages were delayed in the districts of committee members although there was no difference in delinquency rates between committee and noncommittee districts. In these areas, banks delayed the foreclosure starts by 0.5 months (relative to the 12‐month average). The estimated cost of delay to lenders is an order of magnitude greater than the campaign contributions by the political action committees of the largest mortgage servicing banks to the committee members in that period.